The use of role play in the teaching of poems - Kong, Lai Mei (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This action research was carried out to find out if the use role play in the teaching of poems will bring about more opportunities for involvement and participation. It was also to find out if the use of role play promotes interaction and communication as well as enhances understanding of the poems. In this action research a practical teaching session was carried out in a secondary school in Kuching with a group of Form Four students who made up the samples. The researcher was also the teacher of this teaching session. The students were divided into two groups namely; the Control Target Group and the Experiment Target Group. First, the teacher taught the Control Target Group without the use of role play and later the teacher taught the Experiment Target Group with the us. of role play. The poem that was taught was 'The Secret of the Machines' by Rudyard Kipling. Both groups were taught the same poem. While teaching the Experiment Target Group. the teacher made some observations during the Set Induction, Stage 1 and Stage 4 using the Observation Guideline. At the end of the lesson, the students were required to answer eleven questions from the Evaluation Exercise. The instruments for this action research were observation and evaluation exercise. The results from this action research revealed that role play provides opportunities for active students' involvement and participation. It also promotes interaction and communication among the students thus enhancing better understanding of the poem. Together with what role play can offer and suggested recommendations to teachers, it is hoped that teachers will be encouraged and they will try to incorporate role play in the teaching of poems.